2001
DOI: 10.1023/a:1012518831494
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of depression in patients with breast cancer: a comparison between paroxetine and amitriptyline

Abstract: In the context of chronic physical illness, such as breast cancer, depression is associated with increased morbidity, longer periods of hospitalization, and greater overall disability. Prompt diagnosis and effective treatment is. therefore, essential. Several small studies have established the efficacy of tricyclic antidepressants (TCAs) in this setting, and the selective serotonin reuptake inhibitors (SSRIs) would appear to be an alternative therapeutic option because of their established efficacy and better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 35 publications
1
69
3
2
Order By: Relevance
“…Thus, it was shown that taking citalopram and aspirin can positively affect emotional health disorders such as depression. Studies conducted in other countries have also highlighted the significant impact of citalopram on emotional well-being, compared to taking placebos [26,27], while similar studies have recommend the use of SSRIs for similar purposes [28,29]. Aspirin was not studied separately for its effect on emotional well-being, and this study focused on its combined impact with citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was shown that taking citalopram and aspirin can positively affect emotional health disorders such as depression. Studies conducted in other countries have also highlighted the significant impact of citalopram on emotional well-being, compared to taking placebos [26,27], while similar studies have recommend the use of SSRIs for similar purposes [28,29]. Aspirin was not studied separately for its effect on emotional well-being, and this study focused on its combined impact with citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of central serotonergic systems in the etiology of depression is well documented (Pezzella et al 2001). There is evidence that the incidence of depression Fig.…”
Section: Discussionmentioning
confidence: 99%
“…a Apoptotic HT29 cell after incubation with 5-HT 1D antagonist (5 M) for 48 h (green Xuorescence of cell nucleus). b Apoptotic HT29 cell after incubation with 5-HT 1A antagonist (5 M) for 48 h. c Apoptotic HT29 cell after incubation with 5-HT 1B antagonist (5 M) for 48 h. d Comparison of apoptotic index between three test groups and negative control; *P < 0.05; **P < 0.01 increases in patients with cancer, comprising 25% of this sub-population (Huerta et al 2006;Pezzella et al 2001). It seems plausible that introducing phytochemicals which have the most interactions with speciWc monoamine receptors (expressed highly in colorectal cancer tissues) may initiate new approaches in control of this malignancy (Mastrangelo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos controlados mostraram a eficácia antidepressiva também em pacientes com as seguintes doenças: 1) AVE -com a nortriptilina e o citalopram. A fluoxetina teve resultados controversos nesse grupo (Andersen et al, 1994;Gonzalez-Torrecillas et al, 1995;Wiart et al, 2000;Robinson, 2003); 2) diabetes mellitus -com a nortriptilina (embora tenha sido hiperglicemiante nos diabéticos não-deprimidos) (Lustman et al, 1997) e a fluoxetina (Lustman et al, 2000), a melhora do nível glicêmico também ajudou a reduzir os sintomas depressivos em diabéticos (Lustman, Clouse, 2005); 3) no câncer -com desipramina, fluoxetina, paroxetina e amitriptilina (Holland et al, 1998;Pezzella et al, 2001); 4) AIDS -com a fluoxetina e a sertralina (Ferrando et al, 1999;Rabkin et al, 1999); 5) doença de Alzheimer -com a fluoxetina e a sertralina (Petracca et al, 2001;Lyketsos et al, 2003).…”
Section: Qual é O Papel Do Tratamento Farmacológico Da Depressão No Punclassified